Monitoring Pareto Type IV SRGM using SPC - Gutta, Sridevi; Prasad, Satya R (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The Reliability of the Software Process can be monitored efficiently using Statistical Process Control (SPC). SPC is the application of statistical techniques to control a process. SPC is a studyÂ of the best ways of describing and analyzing the data andÂ then drawing conclusion or inferences based on available data. With the help of SPC the software development team can identify software failure process and find out actions to be taken which assures better software reliability. This paper provides a control mechanism based on the cumulative observations of Interval domain data using mean value function of Pareto type IV distribution, which is based on Non-Homogenous Poisson Process (NHPP). The unknown parameters of the model are estimated using maximum likelihood estimation approach. Besides it also presents an analysis of failure data sets at a particular point and compares Pareto Type II and Pareto Type IV models.